Psoriatic arthritis with skin lesions localized to the scalp: A case report. (8th July 2020) - Akaishi, Tetsuya; Yamasaki, Kenshi; Mori, Yu; Takahashi, Toshiya; Izumiyama, Takuya; Terui, Hitoshi; Abe, Michiaki; Takayama, Shin; Aiba, Setsuya; Ishii, Tadashi
Abstract: A 66‐year‐old man with a 2‐year history of suspected scalp eczema with excessive dandruff developed painful swollen joints in the extremities. Four months after developing polyarthritis and polydactylitis, eczema gradually spread to the face. He was referred to our hospital for intractable scalp and facial eczema and polyarthritis. Based on the appearance of the head and facial skin lesions, psoriasis was suspected. Treatment with apremilast (a phosphodiesterase‐4‐inhibitor) was initiated, which swiftly alleviated the skin lesions. The joint deformities persisted, but the pain in the joints disappeared. This case implies that psoriatic arthritis should be suspected even if psoriatic skin lesions are localized to the scalp. Abstract : Psoriatic arthritis was observed in a middle‐aged man with the skin lesions localized to scalp area. Because a delayed diagnosis may result in irreversible joint deformity, close collaboration with dermatologists is essential for early diagnosis of psoriatic arthritis in patients with localized skin lesions remote from the site of arthritis or dactylitis.